Transfer Of Training : The Factors That Affect Its Effectiveness And Its Impact On Worengagement In The Public Sector In Sudan - Elkhedir Ahmed Mousa Abdelgalil
Researchers and practitioners have acknowledged that transfer of training will occur only when trainees have the desire or motivation to transfer training to the job. This study conducted due to the fact that in Sudan public Sector Employee`s there is a little information's known about factors that influence a trainee's decision to use what they have learned on the job. Therefore, this study conducted to achieve three objectives. First, to examine the trainee characteristics factors that influence transfer of training. Second, to examine the work environment factors that influence transfer of training. Third, to examine the impact of the transfer of training on work engagement in the context of public sector in Sudan. The study adopts an analytical, descriptive methodology, and the data of this study has been collected through questionnaire among public sector employees in Sudan, who attended the National Training Program, organized by the Ministry of Human Resources Development, Sudan in 2012 using purposive sampling technique. The questionnaire distributed to 650 of the respondents and 413 of the questionnaire returned with full and completed answers. The data was analyzed using SPSS Version 20. The result from this study present information and practices to improve the abilities of the managers in the public sector organization in Sudan to enhance the employees’ capabilities to transfer the training outcomes after training. However, this study has found that the trainee characteristic factor that influence the transfer of training in Sudan public sector context is organizational citizenship behavior. In addition, this study reveals that there are two work environment factors that have influence on the transfer of training. The factors are perceived organizational support and leader-member exchange. Finally, this study confirmed that there is relationship between transfer of training and work engagement.